Impact of Institutional Quality on Economic Growth - Khokhar, Sara Hussain (2016)
Many researchers believe that a country will undergo economic development when there is progress observed in the Worldwide Governance Indicators (WGI) e.g. there exists mechanisms for the voice and accountability, political stability is high, rule of law prevails and the nation is able to control corruption. The objective of this study is to explore the link between the quality of governance (WGI indicators) and economic growth (GDP). The study attempts to identify the effect of the good governance in the economic development of the Muslim states. A quantitative methodology approach has been adopted, i.e. an econometric model based on the examination of a panel data of good governance indicators for the period of 1996 to 2013. The analysis includes Bangladesh, Indonesia, Iran, Egypt, Pakistan, Lebanon, Malaysia, Turkey and Syria. The study concludes that economic development is positively related to governance. A number of steps have been suggested to improve efficiency of the government and governance structure of the countries.